KEPEMIMPINAN SEBAGAI AMANAH DAN TELADAN DALAM PERSPEKTIF HADIS: IMPLIKASINYA TERHADAP MANAJEMEN PENDIDIKAN ISLAM - Ahmad Naufal; Nurul Masruni; Suraijiah; Fahmi Riady (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the concept of leadership as a trust (amanah) and role model from the perspective of hadith and its relevance to Islamic educational management. Leadership in Islam is not only understood as the ability to manage an organization, but also as a trust that carries moral, social, and spiritual responsibilities toward Allah SWT and human beings. This study employed a qualitative approach using library research. The primary data sources consisted of the hadiths of Prophet Muhammad SAW related to leadership, trustworthiness, justice, and exemplary conduct, while secondary data were obtained from books, scientific journals, and relevant previous studies. Data were collected through documentation techniques, and the data analysis employed content analysis. The findings reveal that leadership in Islam is founded upon the values of trustworthiness (amanah), justice, responsibility, exemplary conduct, and professionalism. The hadiths of the Prophet SAW emphasize that leadership is a great responsibility for which leaders will be held accountable before Allah SWT; therefore, leaders must possess integrity, competence, and noble character. In the context of Islamic educational management, the values of trustworthiness and exemplary conduct can be implemented through the functions of planning, organizing, actuating, and controlling, which are oriented toward justice, transparency, and professionalism. The implementation of these values has been proven to improve leadership quality, organizational culture, and the quality of Islamic education. Thus, leadership based on trustworthiness and exemplary conduct serves as an important foundation for establishing educational institutions that are ethical, professional, and characterized by Islamic values.